Quest for Green‐Solvent Design: From Hydrophilic to Hydrophobic (Deep) Eutectic Solvents - Florindo, Catarina; Branco, Luís C.; Marrucho, Isabel M. (ChemSusChem, 2019)
Deep eutectic solvents (DESs) consist of a mixture of two or more solid components, which gives rise to a lower melting point compared to the starting materials. Until recently only hydrophilic DESs were available, and despite their revolutionary role in the alternative‐solvents field, important issues in chemistry, and chemical engineering (such as water‐related problems and the replacement of toxic volatile organic compounds) could not be tackled. Hydrophobic (deep)—here in parenthesis due to the different depths of the eutectic melting points—eutectic solvents are a subclass of DESs where both components are hydrophobic. The low toxicity, high biodegradability, and straightforward preparation without further purification steps of naturally occurring low‐cost compounds are among the key advantages. Although research on hydrophobic DESs is scarce (the first report was only published in 2015), some interesting features and applications have been reported and deserve to be evaluated and comparisons established. This Minireview is divided into two parts: The first part provides a brief general introduction to DESs and the second part discusses the nomenclature using solid–liquid phase diagram analysis, chemical stability, thermophysical properties comparison, and finally the most important emerging fields of application. Into the deep: This Minireview offers an integrated perspective of the most recent available data concerning hydrophobic deep eutectic solvents (DESs). A critical comparison between hydrophilic and hydrophobic DESs is provided as well as an extensive and complete analysis of development of novel hydrophobic DESs, thermophysical properties, and major areas of interest.